Corrosion behavior and electrochemical corrosion of a high manganese steel in simulated marine splash zone. (10th December 2021) - Yan, Xinyong; Yan, Ling; Kang, Shumei; Qi, Xiangyu; Xu, Meiling; Zhang, Peng
Abstract: The corrosion behavior of a high manganese steel in simulated marine splash zone environment was studied by dry-wet cyclic corrosion experiment and electrochemical experiment. Corrosion kinetics, composition, surface morphology, cross-section morphology, element distribution, valence state, polarization curve and electrochemical impedance spectroscopy were analyzed with the aim of characterizing the characteristics of corrosion product films. The results show that in chloride-containing environment, in the initial corrosion products, Mn oxides with porous structure lead to higher corrosion rate. As corrosion extends, the formation of alloy element oxides in corrosion products changes the corrosion properties of rust layers at different stages. Mo oxides form a stable passivation film, which reduces the influence of chloride ion on corrosion. Ni oxides in the inner rust layer facilitate the transformation of goethite, and Cr oxides in the outer rust layer increase the densification of the rust layer. The stability and compactness of Fe3 O4, α -FeOOH and FeCr2 O4 in the later corrosion products inhibit the corrosion action of manganese iron oxides and slow down the corrosion rate. With the corrosion durations, the corrosion current density of the sample with the corrosion product film first increases and then decreases, and the corrosion potential first moves negative and then shifts in a positive direction subsequently, indicating that the protective effect of the corrosion product film is gradually significant.